Zero-valent isocyanides of nickel, palladium and platinum as transition metal σ-type Lewis bases - Barnett, Brandon R; Figueroa, Joshua S (Chemical communications (Cambridge, England), 2016)
Transition metal complexes that contain metal-to-ligand retrodative σ-bonds have become the subject of increasing studies over the last decade. Lewis acidic "Z-type ligands" can modulate the electronic structure of their resultant complexes in a manner distinct from 2e − donor ligands, and can also engage in cooperative reactivity with a Lewis basic transition metal. In this Feature article, we summarize our work with transition metal isocyanide complexes of group 10 metals that have exploited metal-based σ-type Lewis basicity. While the complexes Ni(CNAr Mes2 ) 3 , Pd(CNAr Dipp2 ) 2 and Pt(CNAr Dipp2 ) 2 were initially targeted as analogues to unstable, low-coordinate metal carbonyls, it soon became apparent that these zero-valent metal centers bore appreciable Lewis basic qualities due largely to the enhanced σ-donor/π-acid ratio of isocyanides compared to CO. Detailed spectroscopic and structural studies of metal-only Lewis pairs (MOLPs) formed from these complexes have furthered our understanding of the electronic structure perturbations effected by Z-type ligand binding. In addition, the platinum (boryl)iminomethane (BIM) complex Pt(κ 2 -N,B- Cy 2 BIM)(CNAr Dipp2 ) has illuminated a general ligand design strategy that can engender significant reverse-dative interactions with buttressed Lewis acids, and also has expanded the known scope of cooperative reactivity that can be realized at a transition metal-borane linkage. Transition metal complexes that contain metal-to-ligand retrodative σ-bonds have become the subject of increasing studies over the last decade.